Hak dan Peran Masyarakat Dalam Reklamasi Tambang PT TIMAH Tbk : Analisis Partisipasi dan Pengawasan - Ramadhan, Himbauan (UNIB Press, 2025)
Mine reclamation is a legal obligation for mining companies to restore the environment after mining operations. This research examines community participation in the management of mine reclamation at PT TIMAH Tbk, focusing on community rights and roles in the reclamation process. The research method uses a normative juridical approach, analyzing laws and regulations and case studies of reclamation implementation in PT TIMAH Tbk's operational areas. The results indicate that although regulations govern community participation in mine reclamation, implementation still faces obstacles such as limited access to information, limited community capacity, and weak oversight mechanisms. This study found that the effectiveness of mine reclamation is highly dependent on the level of active community participation in all stages of reclamation. The study's conclusions emphasize the need to strengthen regulations that guarantee community participation rights and increase community capacity in mine reclamation oversight. Keywords: Comunnity; Participation; Mining; Environment; Reclamation.